The rhythmic logopédica: an alternative for the compensation of the disorders of the language - González León, Yudiana (Revista Universidad de Guayaquil, 2016)
The University is one of the most important cultural institutions in the society, that which is demonstrated in its social and cultural mission: to graduate professionals with an integral general formation that allows him to work in their educational practice, school, and community. In this sense the education in the universities in the pedagogic careers a prepared professional presupposes culturally so that I/you/he/she can influence in a positive way in the students that she will have the responsibility of forming. In this zeal he/she stands out the discipline Artistic Education that contributes to the development of knowledge and the future teachers' abilities and to direct the Musical Education and Plastic Education in the context of the school. From this perspective it is possible to use the Musical Education with their components, specifically the rhythmic education, like an alternative in the activity managed logopédica to the prevention, the diagnosis and the correctioncompensation in the students of the general and special education that present dysfunctions of the language and of the communication, so that in that way they appropriate of tools that allow him to achieve their positive transformation and the maximum development possible of the talkative abilities and of the personality and integration to the family, community, school, labor and social life.
Keywords: Artistic education; Education Musical; rhythmic logopédica; dysfunctions of the language